A National School Health Campaign in Lebanon on Children Aged between 3 and 12 Years Old: Concordance Level between Parents’ Reports and Medical Visit Findings about Physical and Mental Health - Léa Tahan; Peter Habchy; Charbel Moussi; Tia Khadra; Melissa Jawich; Alain Njeim; Ogarite Kattan; Leila Abou Habib; Wassim El Bitar; Béchara El Asmar; Mirna N. Chahine (Children, 2024)
A school’s commitment to promoting health extends beyond students’ efforts to encompass parental involvement and must recognize the critical role of parents in enhancing overall student well-being. This study, conducted in 27 schools across Lebanon, assessed parents’ awareness of their children’s physical and mental health. A school health campaign involved direct medical interventions on 7184 students, followed by phone interviews with 3880 parents to compare their responses with the medical findings. Discordances ranged from extreme mismatches (≥50%) to mild mismatches (<15%), with notable disparities in incomplete vaccination (67.8%), BMI (59%), and mental health indicators (expressions of sadness (69.1%), loneliness (61.0%), and anxiety (53.4%)). Factors such as school type, child’s age, governorate, family income, parents’ occupation, education level, and marital status significantly influenced discordance rates. Notably, mental health aspects exhibited higher disparities, emphasizing the need for improved communication between parents, physicians, and children. Bridging these gaps could empower parents with better knowledge, fostering environments conducive to lifelong healthy behaviors in children. The study underscores the urgency for enhanced communication strategies to bridge discrepancies and ensure a more comprehensive understanding of children’s physical and mental well-being.